Physico-chemical phenomena in thin films and at solid surfaces. - Trakhtenberg, L. I. (Leonid Izrailevich); Lin, S. H. (Sheng Hsien), 1937-; Ilegbusi, O. J. (Thin films and nanostructures, 2007)
The book is devoted to the consideration of the different processes taking place in thin films and at surfaces. Since the most important physico-chemical phenomena in such media are accompanied by the rearrangement of an intra- and intermolecular coordinates and consequently a surrounding molecular ensemble, the theory of radiationless multi-vibrational transitions is used for its description. The second part of the book considers the numerous surface phenomena. And in the third part is described the preparation methods and characteristics of different types of thin films. Both experimental and theoretical descriptions are represented. Media rearrangement coupled with the reagent transformation largely determines the absolute value and temperature dependence of the rate constants and other characteristics of the considered processes. These effects are described at the atomic or molecular level based on the multi-phonon theory, starting from the first pioneering studies through to contemporary studies. A number of questions are included at the end of many chapters to further reinforce the material presented. Unified approach to the description of numerous physico-chemical phenomena in different materials Based on the pioneering research work of the authors Explantion of a variety of experimental observations Material is presented at two levels of complexity for specialists and non-specialists Identifies existing and potential applications of the processes and phenomena Includes questions at the end of some chapters to further reinforce the material discussed.